Correlación de actividades enzimáticas con la respiración basal en suelos cacaoteros del occidente venezolano - Arnaldo Armado; Froilán Contreras; Pablo García; Jorge Paolini (Avances en Química, 2009)
Samples of three cocoa soils from the Venezuelan west, discriminated in six samples of Pedregal farm (Tucaní, Mérida State), four samples of San Juan Lagunillas Experimental Station (Mérida State) and six samples of Chama Experimental Station (Zulia State) were used for determination of enzymatic activities dehydrogenase, arginine amonification (desaminase), acid and alkaline phosphatase, urease, caseinase and β-glucosydase, with the aim of to correlate and compare with the microbiological activity (basal respiration). Enzymatic activities and basal respiration values were higher for soils of Mérida State. Dehydrogenase, urease and caseinase activities there were the most significant correlation (p<0,01) with basal respiration of soils studied.